Perspectives on Arabic Linguistics : Papers from the Annual Symposium on Arabic Linguistics. Volume IX: Washington D.C., 1995. - Eid, Mushira (John Benjamins Pub. Co., 1996)
This volume includes twelve papers selected from the Ninth Annual Symposium on Arabic Linguistics, held at Georgetown University, Washington D.C., 1995. Three of the papers deal with codeswitching with Arabic, two with the acquisition of Arabic, and four with different aspects of Arabic grammatical structure. The volume also includes three papers presenting data on negation in some Arabic dialects (including those of Yemen, Morocco, Egypt). The topics are diverse and include Arabic and constraints on codeswitching, verb embeddings and collocations in codeswitching, ellipsis in child language ac.